2020
DOI: 10.1186/s13036-020-00238-1
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput screening of clinically approved drugs that prime nonviral gene delivery to human Mesenchymal stem cells

Abstract: Background: Human mesenchymal stem cells (hMSCs) are intensely researched for applications in cell therapeutics due to their unique properties, however, intrinsic therapeutic properties of hMSCs could be enhanced by genetic modification. Viral transduction is efficient, but suffers from safety issues. Conversely, nonviral gene delivery, while safer compared to viral, suffers from inefficiency and cytotoxicity, especially in hMSCs. To address the shortcomings of nonviral gene delivery to hMSCs, our lab has prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…However, gene delivery, particularly through nonviral routes, is inefficient. 8,[12][13][14][15][16]24 We have previously reported enhanced nonviral gene delivery to hMSCs by priming with pharmacologic agents, 16 specifically with the glucocorticoid dexamethasone; [13][14][15] however, work remains to improve nonviral gene delivery to hMSCs, in particular through evaluation of key variables of the nonviral gene delivery system. This work systematically compares the key variables of nonviral gene delivery systems (e.g., DNA vector type, DNA vector bacterial elements, promoter, cationic carrier, and donor and tissue source) and the effects of these variables on transfection outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, gene delivery, particularly through nonviral routes, is inefficient. 8,[12][13][14][15][16]24 We have previously reported enhanced nonviral gene delivery to hMSCs by priming with pharmacologic agents, 16 specifically with the glucocorticoid dexamethasone; [13][14][15] however, work remains to improve nonviral gene delivery to hMSCs, in particular through evaluation of key variables of the nonviral gene delivery system. This work systematically compares the key variables of nonviral gene delivery systems (e.g., DNA vector type, DNA vector bacterial elements, promoter, cationic carrier, and donor and tissue source) and the effects of these variables on transfection outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Here, two commercially available transfection reagents were used, which represent both lipid-and polymer-based systems: Lipofectamine 3000 and Turbofect, respectively. These commercially available transfection reagents were chosen as they are readily available, widely used, and have shown moderate levels of transfection in hMSCs [14][15][16]24 (T.K., A.H., and L.S., unpublished data). This study did not include other modes of delivery (e.g., electroporation) given the complexities involved in comparing carrier-based systems to physical methods, but future studies should investigate other delivery strategies in the context of the parameters investigated here.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A primary study compared the therapeutic effects of different mesenchymal stem cells on rheumatoid arthritis in mice, and the authors found that both bone marrow mesenchymal stem cells and umbilical cord mesenchymal stem cells significantly alleviated RA [ 18 ]. Increasingly, recent developments in transfection methods and gene delivery have facilitated the delivery of exogenous DNA or RNA to MSCs to alter gene expression by viral gene delivery systems and gene therapy technologies [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%